Impact Assessment for Developing Countries A Guide for Government Officials and Public Servants - Nakaizumi, Takuya (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
Impact Assessment (IA) is introduced in this book, with a guide to the process, scope, content, and management of IA for the governments of developing economies. In doing so, evidence-based policy making is taken into full consideration. After the principles of IA are set forth, its procedures are described, illustrated by typical cases from the United States and Japan. Then an explanation follows of the components of IA such as necessity, alternatives, and assessment of cost and benefit, with a description of competition assessment. In developing economies, it is not effective to simply import a system from developed countries directly into developing countries, especially for economic regulation and in consideration of compliance and competition issues. Thus the book provides recommendations on how to appropriately modify developed countries' systems for countries that are still developing. The book concludes by taking up several issues surrounding IA, especially nudge theory and public involvement.
Chapter 1 Outline and Necessity of Impact Assessment (IA) -- Chapter 2 Role of Evidence-Based Assessment in Democracy -- Chapter 3 Procedure of Impact Assessment (IA) and Concept of Institution Design for Conducting Impact Assessment (IA) -- Chapter 4. IA Procedure and Organization in the U.S -- Chapter 5. Economists' Role in IA in the United States and the United Kingdom -- Chapter 6. Economists' Optimal Placement Within Relevant Organizations -- Chapter 7 Analysis and viewpoints in Impact Assessment (IA) -- Chapter 8 Role of Causal Inference in IA -- Chapter 9 Competition Assessment in the UK, the US, Japan, and Pakistan -- Chapter 10 Competition Assessment in the US -- Chapter 11: How to Incorporate Behavioral Science and Using Nudges in Regulation and IA -- Chapter 12: COVID-19 Pandemic and Impact Assessment -- Chapter 13 Regulation for the Digital Era and IA for Smart Regulation -- Ch 14. Concluding Remark.
Keywords: Economic development; Law and economics; Economics; Development Studies; Law and Economics; Economics